CORRELATIONS BETWEEN MOTHER’S KNOWLEDGE LEVEL OF EXCLUSIVE BREASTFEEDING AND THE PATTERN IN THE 6-MONTH CHILD IN POSYANDU OF JATIMULYO VILLAGE, PETANAHAN SUB-DISTRICT, KEBUMEN REGENCY, CENTRAL JAVA, INDONESIA - Indriyastuti, Hastin Ika; Utami, Wuri; Juad, Juad (Epidemiology and Society Health Review (ESHR), 2020)
Background: Globally, the infant mortality rate (IMR) is still extremely high. One of the efforts to improve children's health is exclusive breastfeeding for six months. Exclusive breastfeeding can reduce infant mortality rate caused by various infectious diseases. Thus, the community, especially mothers need to have proper knowledge about exclusive breastfeeding, and then they are expected to practice it. This study aims to determine the relationship between mothersâ€™ knowledge of exclusive breastfeeding and the breastfeeding patterns of 6-month children in Jatimulyo Village, Petanahan Sub-district, Kab, Indonesia. Kebumen Regency, Central Java Province, Indonesia.Methods: The study was conducted in Jatimulyo Village using quantitative methods and correlation design with a cross-sectional approach. This study sample consisted of 56 mothers who had children aged 6-24 months selected based on the total sampling approach. Data were analyzed using univariate analysis and bivariate analysis using chi-square statistical tests.Results: This study found that most of the respondents are 26-30 years old and have a high school education level with multigravida parity and have a moderate level of knowledge. The study showed a relationship between the level of exclusive breastfeeding knowledge and breastfeeding patterns with a p-value of 0.002 (<0.05) and a correlation value of 0.499.Conclusions: Therefore, it can be concluded that there is a relationship between the level of knowledge about exclusive breastfeeding and breastfeeding patterns with a p-value of 0.002 (<0.05) and a correlation value of 0.499.Â